Comparative efficacy of targeted maintenance therapy for newly diagnosed epithelial ovarian cancer: a network meta-analysis - Xu, Xiaoyu (Cancer Manag Res, 2019)
Background: The number of published randomized clinical trials (RCTs) using targeted maintenance therapy for newly diagnosed epithelial ovarian cancer is increasing. Our objective was to evaluate the comparative effectiveness of each maintenance therapy using a network meta-analysis. Materials and methods: A systematic search for RCTs was conducted using Medline, Embase, and CENTRAL databases followed by a Bayesian network meta-analysis. The primary outcome was progression-free survival (PFS) and the secondary outcome was overall survival (OS). Pooled hazard ratios (HRs) with 95% credible intervals (95% CrIs) were used to estimate outcomes. Results: A total of 11 RCTs involving 6631 patients were included. Network meta-analysis showed that pure maintenance therapy with pazopanib resulted in a significantly better PFS compared with placebo (HR, 0.77; 95% CrI, 0.65–0.92). Bevacizumab-throughout treatment was also associated with a better PFS (HR, 0.76, 95% CrI, 0.69–0.84). However, anti-CA-125 monoclonal antibodies (abagovomab and oregovomab) showed no significant survival benefit. Moreover, combined analysis showed that targeted-throughout was not significantly superior to pure targeted maintenance therapy for PFS and OS. Stratified analysis showed paralleled results with no significant difference between pazopanib pure maintenance and bevacizumab-throughout treatments. Conclusion: Our study showed a survival advantage conferred by pazopanib and bevacizumab as maintenance therapy in newly diagnosed epithelial ovarian cancer. Further clinical trials are essential to both determine the effect of bevacizumab in the maintenance stage and identify the specific subgroup(s) that benefit.